Assessing the knowledge, attitudes and practices of physicians on antibiotic use and antimicrobial resistance in Iran: a cross-sectional survey - Ramin Sami; Raheleh Sadegh; Fataneh Fani; Vajihe Atashi; Hamid Solgi (Taylor & Francis Group, 2022)
Background Antimicrobial resistance (AMR) is a global public health issue. Physicians should play a key role to fight AMR, and medical education is a fundamental issue to combat it. Understanding the knowledge, attitudes and practices of physicians regarding antibiotic prescription and antibiotic resistance is fundamental for controlling the irrational antibiotic use. This study was conducted to assess the knowledge, attitudes and the practices of physicians in Iran with respect to antibiotic resistance and usage. Methods A cross-sectional study was performed from June to October 2021 among physicians at primary care centers and academic hospitals in the region of Isfahan, Iran. A total of 182 physicians were surveyed. Participants were invited to complete a self-reported questionnaire (paper based or online questionnaire). The questions were based on knowledge, attitude, and practice toward antibiotic usage and AMR. Data were analyzed using SPSS version 18 software following the objective of the study. Results Out of 182 study participants, 100, 50 and 32 responders were medical doctors (MD), internist and other specialists, respectively. Regarding the knowledge section of the questionnaire, almost less than 10% of participants declared to know the antibiotics of Iran's antimicrobial stewardship program. Also, the percentage of participants who correctly responded to clinical quizzes was 23% for treatment of extended-spectrum beta-lactamase (ESBL) producers, 59.3% about the treatment of severe sepsis, 22% about the intrinsic resistance of Proteus mirabilis and 43.4% for experimental treatment with vancomycin in community-acquired pneumonia. Regarding attitude, most participants (97.2%) were aware of the antimicrobial resistance problem in Iran, and 95.6% agreed that prescribing antimicrobials was not the appropriate in our country. Regarding practice, only 65.9% of participants said that before prescribing antibiotics they use of local and international antimicrobial therapy guidelines and less than 50% of physicians were in contact with a microbiology laboratory. Conclusion This data revealed that our physicians' level of knowledge about AMR and antimicrobial stewardship is poor, so there is the need to increase training on antibiotic resistance and antimicrobial stewardship.